2020
DOI: 10.1002/csr.1993
|View full text |Cite
|
Sign up to set email alerts
|

The importance of corporate social responsibility in achieving high corporate reputation

Abstract: Increased global competitiveness has forced corporations to improve how they manage their resources, especially when it comes to resources that give them a competitive advantage. Corporate Reputation and Corporate Social Responsibility fulfill that role. This research aims to identify the dimensions that most influence Corporate Reputation and which can be most easily used to achieve a positive result. To do this, the data about 46 companies (from different sectors) contained in the 2015 report "The world's mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 40 publications
1
36
0
4
Order By: Relevance
“…Our findings are in line with Forcadell et al (2020) who established a strong relationship between reputation and stakeholders' trust and confirmed previous research insights by demonstrating the reputation controversies and its potential positive impact on customers' behaviour (W. Ali et al, 2017;Barnett, 2019;Li et al, 2019;Sánchez-Torné et al, 2020).…”
Section: Measurement Model Assessment and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in line with Forcadell et al (2020) who established a strong relationship between reputation and stakeholders' trust and confirmed previous research insights by demonstrating the reputation controversies and its potential positive impact on customers' behaviour (W. Ali et al, 2017;Barnett, 2019;Li et al, 2019;Sánchez-Torné et al, 2020).…”
Section: Measurement Model Assessment and Discussionsupporting
confidence: 91%
“…Many research studies have demonstrated the positive impact that holding a favourable reputation can have in different corporate areas. In this view, corporate reputation represents a source of goodwill (Feldman et al, 2014;MacMillan et al, 2005) and a statement of value and commitment (Sánchez-Torné et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, if social media reports firms' environmental protection behaviors, it would send positive signals to the public that firms willingly undertake environmental protection responsibility. Existing literature already confirms that social responsibility activities act as enablers to firms' brand credibility, reputation, and financial performance (Eberle et al, 2013;Hur et al, 2014;Sánchez-Torné et al, 2020). According to signaling theory, there appears information asymmetry between firms and external stakeholders.…”
Section: Media Coverage and Environmental Randdmentioning
confidence: 98%
“…Last, environmental information disclosure and social supervision make it easier for the public to know about firms' environmental or polluting behaviors. As noted above, social responsibility activities are positively associated with firms' reputation and financial performance (Hur et al, 2014;Sánchez-Torné et al, 2020). Furthermore, engaging in environmental protection brings economic benefits to firms (Muzhar et al, 2020;Saeidi et al, 2015).…”
Section: The Environment Protection Law and Environmental Randdmentioning
confidence: 99%
“…Este hecho otorga un papel crucial a los modelos de medida de Rasch en la metodología aplicada en las ciencias sociales (Cliff, 1992;Michell, 1999), siendo empleados en psicología, educación, economía aplicada, salud pública, etc. Un ejemplo reciente de su empleo en el ámbito del análisis de empresas es el artículo de Sánchez-Torné et al (2020) en el que se cuantifica la Responsabilidad Social Corporativa para empresas en base a un conjunto de ítems. Otro ejemplo claro sería Pérez-Conde et al (2020) en el cual se analizan los puntos fuertes y los puntos débiles de una muestra de municipios, jerarquizando la posición de los mismos en un continuo lineal y poniendo de manifiesto las posibilidades de mejora de los mismos.…”
Section: Introductionunclassified